Academic Stress, Psychological Well-being and Academic Achievement among College Students - Alina Saleem, Bushra Akram (Pakistan Journal of Psychology, 2018)
The current study explored the relationship of demographic variables, academic stress, and psychological well-being with academic achievement among college students. Sample of total 350 college students (132 male & 218 female) from private and government colleges was selected through stratified random sampling technique. The Educational Stress Scale for Adolescents (Dunne, Sun, Hou, & Xu, 2011), Psychological Well-being Scale (Aslam & Kausar, 2010), and obtained marks in last examination were used to measure study variables. Hierarchical multiple regression analysis revealed that demographic variables (gender, educational level (first year/second year), organization (private/government), academic stress (worry about grades) and psychological well-being (personal growth) accounted for 89% variance in the scores of academic achievement. These findings provided a better indication of what is operative in promoting the psychological well-being to increase the academic outcome of students.